Search for Leptoquarks Coupled to Third-Generation Quarks in Proton-Proton Collisions at root s=13 TeV - Sirunyan, A. M. (2018)
Three of the most significant measured deviations from standard model predictions, the enhanced decay rate for B -> D-(*())tau nu, hints of lepton universality violation in B -> K-(*())ll decays, and the anomalous magnetic moment of the muon, can be explained by the existence of leptoquarks (LQs) with large couplings to third-generation quarks and masses at the TeV scale. The existence of these states can be probed at the LHC in high energy proton-proton collisions. A novel search is presented for pair production of LQs coupled to a top quark and a muon using data at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb(-1), recorded by the CMS experiment. No deviation from the standard model prediction has been observed and scalar LQs decaying exclusively into t mu are excluded up to masses of 1420 GeV. The results of this search are combined with those from previous searches for LQ decays into t tau and b nu, which excluded scalar LQs below masses of 900 and 1080 GeV. Vector LQs are excluded up to masses of 1190 GeV for all possible combinations of branching fractions to t mu, t tau and b nu. With this analysis, all relevant couplings of LQs with an electric charge of -1/3 to third-generation quarks are probed for the first time.